Effective Organizational Development for Students of Bina Amanah Cordova Entrepreneurship School - Dorina Widowati; R. Rosiyana Dewi; Nurhayati; Andjani Putri Ramadhani (CV. AFDIFAL MAJU BERKAH, 2024)
Micro, Small, and Medium Enterprises (MSMEs, UMKM in Bahasa Indonesia) are vital to the economy, serving as key job creators and contributors to national income and economic recovery (Martínez-Olvera, C, 2019; Darwin, 2018). However, SMEs face challenges like limited funding, inadequate human resource management, technological shortcomings, raw material constraints, and marketing difficulties (Sulistia Teg, 2012). The School of Entrepreneurship Trust Cordova (SKBAC) provides a one-year entrepreneurial training program for young people and college dropouts, free of charge. Participants, some of whom already have businesses like food stalls or jewelry, gain knowledge in business management. The Faculty of Economics and Business of Trisakti University has partnered with SKBAC since 1998, offering a program on capacity building and effective organizational development. The latest session was held on December 17, 2023, at SKBAC, Japos Raya, Pondok Jati, Tangerang South, Banten. The training focused on strategies for effective organizational development. Evaluations showed that SKBAC students, both current and aspiring entrepreneurs, found the training useful and relevant. Participants gained confidence in improving their businesses' performance and revenue. The program was successful and beneficial to participants, the community, and the organizers, with recommendations for further training and support for SKBAC students. entrepreneurs